Manganese-Based Prussian Blue Nanocatalysts Suppress Non-Small Cell Lung Cancer Growth and Metastasis via Photothermal and Chemodynamic Therapy - Fang, Danruo; Liu, Zeyu; Jin, Hansong; Huang, Xiulin; Shi, Yongxin; Ben, Suqin (Frontiers in Bioengineering and Biotechnology, 2022)
Based on the safety of prussian blue (PB) in biomedical application, we prepared manganese-based prussian blue (MnPB) nanocatalysts to achieve enhanced photothermal therapy and chemodynamic therapy. And we conducted a series of experiments to explore the therapeutic effects of MnPB nanoparticles (NPs) on non-small cell lung cancer (NSCLC) in vivo and in vitro. For in vitro experiments, the MnPB NPs induced apoptosis of A549 cells by reactive oxygen species upregulation and near-infrared irradiation. Moreover, the MnPB NPs could inhibit lung cancer metastasis through downregulating the matrix metalloproteinase (MMP)-2 and MMP-9 expression in A549 cells. And for in vivo experiments, the MnPB NPs inhibited the growth of xenografted tumor effectively and were biologically safe. Meanwhile, Mn2+ as a T1-weighted agent could realize magnetic resonance imaging-guided diagnosis and treatment. To sum up, the results in this study clearly demonstrated that the MnPB NPs had remarkable effects for inhibiting the growth and metastasis of NSCLC and might serve as a promising multifunctional nanoplatform for NSCLC treatment.